Container Port Development Projects on The Java Sea, Indonesia - Bambang Adhi Priyambodho (JURUSAN TEKNIK SIPIL, 2016)
Port Development Projects have a some positive and constructive conclusions, combined with certain recommendations, but only if I am familiar with, and have explored, all kinds of values in port development. I will explain the underpinning a potential problem in more detail and how it can be used, and of value, in world port cities where several common problems occur: particularlymatters relating to economic growth, climate change and urbanisation.First, economic growth and development are two of the essentials of the world’s economy. They allow developing countries to trade abroad the commodities of their homeland and raise their economic standards. Fundamentally, the development of an economy and its accompanying population usually goes along with the increasing of quantities and infrastructures of ports[1]. This commercial advancement potential forms opportunities for port expansion, so allowing the port owner (s) to gain an increased number of benefits. In addition, since the port serves as a backbone of economic growth, it is very important to address this capacity problem in order to enlarge the growth of the national economy. Economic growth has several values over and above economics, such as reputational and societal.Second, climate change is a big challenge to ports, both in developing and developed countries. The threat of flooding is imminent to those countries which are located in low-lying areas and deltas. Climate change engenders several effects, such as increased sea water levels (SWL), river floods, high waves, atmospheric greenhouse gases and tropical cyclone activities; all of whichcould devastate coastal areas and transportation systems. These effects will increase the number of climate-related risks, causing loss of life, social disruption and decreased economic standards and levels of activity. However, recent research revealed t hat, at this moment, a few port authoritieshave started to handle, or at least confront, the issue of climate change [1,2]. Climate change impacts have several dimensions such as safety, sustainability and accessibility.Third, the process of urbanisation is very important. This process, in fact, will increase the excess of water surface run off, including maximum and minimum flows. The first indicators have shown that increasing land use is causing a decrease in water infiltration. This influence is crucial to be recognized as it will greatly impact water quality and ecosystems [3-5], urbanisation’s embrace and impact several values such as safety, societal and accessibility.In this paper will be on the Indonesia’s port cities, and the potential conflicts arising between the port and city. One of the major challenges now, and in the future, is to balance and reconcile different values, as well as to find innovations which satisfactorily cover more than one value at a time. The aim of this research is to investigate how to effectively balance and reconcile different identified values and the conflicts which arise between port and city. In section 3-6, I will explaining what theory and references are used in this paper